BDS-3 RDSS two-way time transfer with asymmetric delay compensation model. (1st March 2023) - Ren, Zhiling; Huang, Xinming; Gong, Hang; Peng, Jing; Sun, Guangfu
Abstract: In the BeiDou navigation satellite system-3 (BDS-3) radio determination satellite service (RDSS), there exists a natural two-way link between the center station and the user site that can be used to achieve time transfer. Traditionally, RDSS two-way time transfer is realized by analogy with the two-way satellite time and frequency transfer (TWSTFT) technique. However, unlike TWSTFT, the signal propagation delays are not completely symmetrical in the RDSS two-way link because of the differences in signal emission time. In this study, a model of two-way time transfer with BDS-3 RDSS is presented. An asymmetric delay compensation method is introduced to solve the asymmetry of RDSS signals and improve the accuracy of two-way time transfer. In addition, BDS-3 RDSS common clock difference experiments are designed to test the performance of two-way time transfer with an asymmetric delay compensation model. Based on analyses of the experimental results, three conclusions can be drawn. First, the accuracy of RDSS two-way time transfer is improved when the asymmetric delay compensation model is applied. Second, BDS-3 RDSS two-way time transfers in different in-station beams and subbands do not show many discrepancies on the whole, and the standard deviation values of the BDS-3 RDSS time transfer results range from 1.7 ns to 2.6 ns for the test signals. Third, the two-way time transfer results are not generally affected by receiver coordinate errors.